Sistem Pengelolaan Kegiatan Magang Mahasiswa Polman Negeri Babel - Alakbar Yusa, Umayu; Agita Rindri, Yang; Mubaroh, Sari (Jurnal Inovasi Teknologi Terapan, 2023)
Students at Polman Negeri Babel carry out internships in semester 6 for Diploma III and semester 8 for Diploma IV. In internship activities, there are several processes including the process of submitting, implementing, monitoring, apprentice siding, and grading which still apply conventional processes. Many problems often occur as a result of conventional internship management, including data loss, document duplication, and difficulty in obtaining information about student internships. Based on the problems that have been described, it is necessary to conduct research with the aim of designing and developing a system of student internship activity management that can solve these problems. Data collection methods in this study apply interview and observation methods. For the design method, the authors apply the prototype method with the aim of facilitating research work that adapts to user needs. The testing method is carried out using black box and beta testing methods. The results of black box testing on the student internship activity management system that has been developed show that 100% of the system functionality is running as expected. Meanwhile, based on the results of testing with beta testing, the results showed 88%.